Analysis of the Halaqah Study Program on Character Formation at Boarding School based on CIPP Model - Basri, Hasan; Mania, Sitti; Rasyid, Muhammad Nur Akbar (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The necessity to assess the halaqah religious study program's impact on Islamic boarding school students' religious character, discipline, and responsibility prompted this research. Despite the program's long history, there has been no systematic examination of its fit with the madrasah's vision and objective and its impact on student character development. This study intends to evaluate the halaqah religious study program using the CIPP (Context, Input, Process, Product) model, focusing on program suitability, implementation, and character development outcomes. The research method used was qualitative, with data collection techniques through in-depth interviews, observation, and documentation. Research informants included the madrasah principal, supervising teachers, students, parents, committee administrators, and alumni in the Madrasah Tsanawiyah As'adiyah Puteri Pusat Sengkang. The evaluation results indicated that the halaqah program follows the madrasah's vision and mission and consistently develops Islamic character. Competent and experienced supervisors, supporting infrastructure, and different recitation methods help the program succeed. Students' good attitudes and religious conduct rise with positive parent and student reactions. Madrasas should raise the frequency and quality of halaqah (Islamic gatherings), teacher training, and stakeholder support for program sustainability based on these findings. This study focused on one madrasah and used qualitative methods; hence, a larger study using mixed approaches is necessary for more comprehensive results.